AgroTutor Academy: annual report - Kiragi, Pratibha Suresh (CGIAR Initiative on Digital Innovation, 2024)
Farmers in the Global South face significant challenges in accessing tailored educational resources to enhance their skills in critical areas such as communication, market access, and resource management. Traditional training programs often lack accessibility, personalization, and adaptability to cater to the diverse needs of small-scale and large-scale farmers. This results in a gap between the available knowledge and the practical skills required to navigate modern agricultural challenges effectively. There is a need for an inclusive, scalable, and user-friendly learning platform that provides personalized, context-specific education while accommodating the technological and connectivity constraints of rural regions. Dedicated to enhancing the skills of the last-mile beneficiaries in the Global South, the AgroTutor Academy of the ICTforAg Learning Network, offers courses on critical areas such as communication, market access, and resource management, catering to both small-scale and large-scale farmers. Delivered through WhatsApp and online mode on a 1:1 basis, the courses provide a personalized learning experience that tracks individual progress to customize content based on evolving needs.